El Debate Moderno Sobre Los Escritos Económicos Aristotélicos - Borisonik, Hernán (The modern debate on the Aristotelian economic writings., 2013)
The present article is a critical reading of the most important modern interpretations on Aristotle's economic writings. Firstly, the debate between the “primitivists" and the “modernists" (headed by Rodbertus, Bücher and Meyer) will be studied. Then, the readings of Karl Marx, Joseph Schumpeter, Karl Polanyi and Moses Finley, will be analyzed, considering these authors as the most renowned commentators of the Aristotelian economical legacy. (English)
Political Science
Keywords: ARISTOTLE; Aristóteles; FINLEY; M. I. (Moses Israel); 1912-1986; MARX; Karl; 1818-1883; SCHUMPETER; Joseph Alois; 1883-1950; economic research; economics; economía; history of economics; primitivism and modernism; primitivismo y modernismo